(3GdQhVI GdHgjI aj TQM GddeYI GdOeTbjIs - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s ((3eTgO Ydj Hf ehSi GdQVGs)
(3ChdgG (B:s
.. (3GdGTQGb Ydi GdXGgQ eY LaGa GdLejY HNdGa GdeJYOO GdeJdGUb EPG CTQbJ Ydi HYVg hGdfGQ eG CMGdJg QeGOG Ch ONGfG dG NRaG hBNQG aj CUM Gdbhdjf (B..s
(3BNQgG (B:s
.. (3hGdCbhi VeGf GdeaQW efge Ohf ZjQg hGdQhGjI McGjI hGbYI eMJedI ddJChjd hdjcf gPG BNQ GddeYI hde fPcQ ajgG Shi Gdege ef GdCMcGe hgh eTghQ Hjf GdCUMGH (B.. (3BNQ cdGe GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\ 64s
(3GdPQjYI (B11/1757 (209)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis